Trophic Ecology of Breeding White-Headed Steamer-Duck (Tachyeres leucocephalus) - Agüero, Maria Laura (2014)
White-headed Steamer-Ducks (Tachyeres leucocephalus) are flightless waterfowl endemic to a small section of coastline in Patagonia, Argentina. This study provides the first detailed information on White-headed Steamer-Duck diet composition, foraging behavior and prey availability. This study was conducted in the northern San Jorge Gulf, Patagonia, during 2007. Fifteen feeding territories were identified, and food availability was quanti- fied within them and also within unused areas. A total of 45 feces were analyzed to determine diet composition, and foraging behaviors of females were monitored. Benthic community diversity differed between territories and non-territories. Overall, diversity and invertebrate abundance tended to be higher in territories. Ten invertebrate prey taxa were identified in adult diets, and the most frequent prey in feces were crabs, mussels, and ragworms. Head-neck dipping was the most common method of feeding. Our results improve the understanding of the relationship between diet, selection of areas with special invertebrate availability and foraging techniques used to access and exploit the resources.